2010
DOI: 10.1097/jto.0b013e3181e0b977
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Lung Cancer with Low-Dose Computed Tomography: A Systematic Review and Meta-Analysis of the Baseline Findings of Randomized Controlled Trials

Abstract: Objectives Lung cancer is the leading cause of death among all cancers. An estimated 29% of the global population older than 15 years currently smokes tobacco. The presence of a high risk population, relatively asymptomatic nature of the disease in the early phase, and relatively good prognosis when discovered early makes screening for lung cancer an attractive proposition. We performed a systematic review and a meta-analysis of the baseline results of randomized controlled trials so far published, which inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…The Canadian experience from 2003 to 2005, one of the branches of the famous International Early Lung Cancer Action Program, demonstrated that 75 % of the detected patients (15/20) were in stage I and 70 % (14/20) received surgical excision [12], which were consistent with others [14,30,31]. Similarly, our study revealed 77.42 % (24/31) of screened patients were in stage I.…”
Section: Discussionsupporting
confidence: 80%
“…The Canadian experience from 2003 to 2005, one of the branches of the famous International Early Lung Cancer Action Program, demonstrated that 75 % of the detected patients (15/20) were in stage I and 70 % (14/20) received surgical excision [12], which were consistent with others [14,30,31]. Similarly, our study revealed 77.42 % (24/31) of screened patients were in stage I.…”
Section: Discussionsupporting
confidence: 80%
“…Most LDCT lung cancer screening trials present results for baseline and incidence screening rounds separately and elaborate reviews of this data were published before (4,5,17,18). Although comparing screening rounds provides valuable information about a trial's lung cancer screening performance in general, this approach does not appreciate the possible differences among nodules firstly detected during baseline and incidence screening rounds and is heavily influenced by the methodological differences of the respective LDCT lung cancer screening trials.…”
Section: Review Articlementioning
confidence: 99%
“…104 Early randomized control trials in lung cancer screening evaluated chest radiography with or without sputum cytology and showed no reduction in lung cancer mortality. [105][106][107][108][109] The lack of a clear result from chest x-ray screening and the refinement of CT scanning techniques have led to the evaluation of CT for lung cancer screening.…”
Section: Screeningmentioning
confidence: 99%